Spectroscopy of Alpha-Particles Using the Thermally Diffused p-i-n Detector - Abdulhadi, Abduljalil E.; Alhoweij, Haniya Saleh (Scientific Journal for Faculty of Science-Sirte University, 2023)
The goal of this experimental work is to learn more about the characteristics of alpha particles, how they interact with matter, and their range.. A thermally diffused detector and a triple alpha source with the isotopes Pu-239, Am-241, and Cm-244 were employed in the experimental work. The primary aim was to obtain three main energy peaks and then determine the absolute activities of these isotopes. The absolute activities were calculated, and they were 1652.38±40.6 Bq, 936.38 ±30 Bq, and 706.8±26 Bq for Pu-239, Am-241 and Cm-244 respectively. The second aim was to calibrate the Multi- channel analyser at lower energies known as attenuation output using the initial pulser peak that covered the Am-241 peaks at an energy of 5.49MeV. The FWHM was estimated using counting statistics to be 11.23.35 kev. Then, it was determined when the alpha emission for three isotopes started to stop, using an extrapolated range of alpha particles. In order to draw the graphs of each radioisotope's peak energy versus air pressure and the FWHM versus six spectra of gas pressures, air pressures of various m-bar air pressures were measured. The procedure should ultimately be completed by measuring the intensity of -particles and documenting the peak count rate for a particular element, in this case Cm-244.